Oregano Essential Oils Mediated Intestinal Microbiota and Metabolites and Improved Growth Performance and Intestinal Barrier Function in Sheep - Jia, Li; Wu, Jianping; Lei, Yu; Kong, Fanyun; Zhang, Rui; Sun, Jianxiang; Wang, Liao; Li, Zemin; Shi, Jinping; Wang, Ying; Wei, Yubing; Zhang, Ke; et al. (Frontiers in Immunology, 2022)
With the increased demand for safe and sustainable alternatives to growth promoting antibiotics in the livestock industry, oregano essential oils (OEO) and Lactobacillus reuteri (LR) have been examined as alternatives to antibiotics for growth promotion and to improve animal health and performance. However, the mechanism underlying the OEO and LR mediation of sheep growth remains unknown. In this study, 16S rRNA gene sequencing and untargeted metabolomics were used to determine the role of the gut microbiota in the growth improvements observed. The potential modulating roles of intestinal microbial metabolites of OEO and LR to intestinal health were systematically explored as well. It was observed that both OEO and LR had greater average daily gain (ADG) and lower F/G ratio (P < 0.001). Furthermore, OEO also appeared to have produced a greater amylase enzyme activity and mucin gene expression in the jejunal mucosa (P < 0.01). It was also observed that OEO reduced serum IL-2 and TNF-β as well as mRNA levels of IL-6 in the jejunal mucosa (P < 0.05). Moreover, dietary OEO supplementation increased the abundances of Ruminococcus, Bifidobacterium and Enterococcus, while the relative abundances of Succiniclasticum, Marvinbryantia and Streptococcus were enriched in LR group. Spearman’s correlation analysis revealed that the abundances of Bifidobacterium, Ruminococcus and Enterococcus were positively correlated with the mRNA expression of mucins. Moreover, the relative abundance of Enterococcus was positively correlated with amylase activity (P < 0.05). Metabolomics analysis indicated that OEO and LR increased the levels of indole acetaldehyde and indole-3-acetic acid through the tryptophan metabolism pathway. It was observed that LR also decreased the inflammatory metabolites including tryptamine and 5-hydroxyindole-3-acetic acid. Collectively, these results suggested that OEO exerted a beneficial effect on growth performance and the mucosal barrier, and affected tryptophan metabolism and improved the intestinal microbiota of sheep.